Pseudo-ductile fracture in grid stiffened structure by automated fibre placement. (15th March 2023) - Zhao, Cong; Donough, Matthew J.; Prusty, B. Gangadhara; Xiao, Jun; Zhou, Laishui; An, Luling
Graphical abstract: Highlights: Pseudo-ductility was achieved via glide of cut-tows in thick stiffener. Optimal design of cut-tows in AGS was obtained under bending and tension. Design limit of composite AGS was pushed with the method proposed in this paper. Pseudo-ductile fracture induced by cut-tows provided repair window for AGS. Abstract: Pseudo-ductile fracture in composite structures is desirable which can provide a window of detection for structural anomaly. Several design strategies had been investigated to induce pseudo-ductile fracture in thin composite laminates. However, the thickness of load bearing structures such as the grid stiffeners in advanced grid structures are ranged up to 30 mm. This paper presents an investigation into introducing pseudo-ductile fracture into a grid stiffener of representative thickness by implementing cut-tow design at the grids' intersection. Automated fibre placement permits the cutting, terminating and restarting layup of a tow which makes this design feasible. Experimental and numerical results showed the benefits of a cut-tows design is twofold. Firstly, improvements up to 42.4 % was achieved in mechanical strength due to the reduction in tow waviness at the grid's intersection. By varying the ratio and distribution of cut-tows, it is possible to achieve additional 55.9 % of pseudo-ductile displacement before fracture in thick section grid stiffeners under tension and bending loads. The enabling mechanism of pseudo-ductile fracture are discussed further using numerical modelling.